Preparation method and application of modified iridium ruthenium titanium mesh electrode
By incorporating [Emim]BF4 and bismuth nitrate into the iridium ruthenium titanium electrode, the catalytic activity and service life of the modified iridium ruthenium titanium mesh electrode have been improved, and the catalytic efficiency of the existing electrodes in high-pollution wastewater treatment is solved. The problem has achieved efficient degradation of difficult-to-degrade organic matter.
Patent Information
- Application Number
- CN202411671760.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When using high-pollution wastewater, the existing iridium ruthenium titanium electrodes have insufficient catalytic efficiency and are difficult to effectively degrade organic matter.
[Emim]BF4 and bismuth nitrate were incorporated into the IrO2-RuO2 coating by thermal decomposition method to prepare a modified iridium ruthenium titanium mesh electrode to improve its catalytic activity and service life.
The activity and service life of the modified iridium ruthenium titanium mesh electrode are significantly improved, and the degradation efficiency of difficult-to-degrade organic pollutants is enhanced.
Smart Images

Figure CN119490252A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water pollution treatment, and specifically relates to a preparation method and application of a modified iridium ruthenium titanium mesh electrode. Background Art
[0002] Electrocatalytic oxidation technology has become a research hotspot in the current wastewater treatment field due to its advantages such as strong ability to degrade organic matter, simple operation and maintenance, clean and controllable, small footprint, and can be combined with other technologies. The anode is the core area of electrocatalytic oxidation degradation of pollutants, and the research and development of high-performance anode materials is the key to improving electrocatalytic oxidation technology. Iridium-ruthenium-titanium electrode is an electrode with a surface active layer of IrO2-RuO2. Iridium-ruthenium-titanium electrodes are widely used in actual wastewater treatment due to their excellent catalytic performance, good mechanical properties, corrosion resistance, and long working life. However, electrodes with pure iridium-ruthenium coatings also have some defects and shortcomings such as easy cracking, and the electrocatalytic efficiency cannot meet the needs of some wastewaters with high pollutant concentrations and high emission standards. The active layer can be modified to improve the catalytic performance of the active layer by adjusting the element ratio of the active layer, introducing a multi-layer coating, or doping with new substances. Therefore, it is of great significance to develop iridium-ruthenium-titanium electrodes with better performance for difficult-to-degrade organic matter in wastewater. Summary of the invention
[0003] In order to improve the catalytic performance of the IrO2-RuO2 active layer, the present invention provides a preparation method and application of a modified iridium ruthenium titanium mesh electrode. The invention pre-treats the titanium mesh, and then adds [Emim]BF4 and bismuth nitrate into the IrO2-RuO2 coating by thermal decomposition to prepare a modified iridium ruthenium titanium mesh electrode. The activity and service life of the modified iridium ruthenium titanium mesh electrode are significantly improved, thereby improving the degradation performance of refractory organic matter in wastewater.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] Step 1, pretreatment of the electrode substrate. The electrode is based on titanium mesh. Polish with 180, 400, and 800 grit sandpaper to remove the surface oxide layer, and ultrasonically clean it in pure water for 10 minutes. Put the mesh into a 10% sodium hydroxide solution by mass, boil it at 85°C for 2 hours to remove the oil stains on the surface of the mesh. Wash the mesh repeatedly with pure water, and soak it in a 10% oxalic acid solution at 85°C for 2 hours to make the surface of the titanium mesh uneven, and even pitting, and completely remove the oxide layer on the surface of the titanium mesh, so that the titanium mesh has a uniform and rough surface. Finally, rinse the titanium mesh with pure water, and store the pretreated titanium mesh in a 1% oxalic acid solution by mass.
[0006] Step 2, preparation of electrode oxide coating. The electrode oxide coating is prepared by thermal decomposition. A certain amount of ruthenium trichloride and chloroiridic acid are dissolved in n-butanol to ensure that the mass (g) of the total compound is 1:50 to the volume (mL) of n-butanol, and the mass ratio of the ruthenium trichloride and chloroiridic acid is 2:1. Add an appropriate amount of bismuth nitrate to always keep the concentration of bismuth nitrate in the coating liquid at 1mmol / L. Add an appropriate amount of ionic liquid [Emim]BF4, the concentration of [Emim]BF4 in the coating liquid is 2.35mmol / L, ultrasonically vibrate for 20min to fully dissolve it, and stir evenly for 1h to prepare the required coating liquid. After the pretreated spare titanium mesh is cleaned and dried with pure water, the prepared coating liquid is evenly brushed on the titanium mesh with a brush, and quickly moved into a 105°C drying oven for 10min, and then moved into a 450°C muffle furnace for high-temperature calcination for 15min. The above operation is repeated 10-20 times until the coating liquid is used up. Finally, the modified iridium-ruthenium electrode was prepared by calcining at 450° C. for 1 h in a muffle furnace and cooling to room temperature.
[0007] Step 3, electrocatalytic degradation experimental conditions. Organophosphine agents are used in huge quantities every year, and they have excellent scale inhibition performance, low cost, and are applicable to a wide range of water quality. However, such organic matter has high chemical stability and is not easy to hydrolyze. While aggravating water pollution, it will also chelate heavy metal ions, hinder precipitation formation, and increase the risk of eutrophication. Its environmental effects cannot be ignored. Among them, 1-hydroxyethylidene-1,1-diphosphoric acid (HEDP) is a typical organophosphine scale inhibitor in reverse osmosis concentrated water. Traditional biological and physicochemical methods have poor degradation efficiency for such organic agents, and it is difficult to effectively remove them fundamentally. Therefore, the present invention selects HEDP as the target pollutant for the electrocatalytic degradation experiment. The conditions for electrochemical treatment are constant current, the anode plate is a modified iridium ruthenium titanium mesh electrode, the cathode is a titanium mesh electrode, the electrode size is 10cm×10cm, the diamond mesh size on the cathode plate and the anode plate is 5mm×10mm, and the distance between the two plates is 3cm. 550 mL of HEDP solution with an initial concentration of 50 mg / L was placed in the electrolytic cell, 0.25 mol / L NaCl was used as the electrolyte, and the electrode working area was 5 cm × 10 cm. The current density was 30 mA / cm 2 Electrocatalytic oxidation degradation.
[0008] Compared with the prior art, the present invention has the following beneficial effects:
[0009] (1) The present invention uses a heat treatment method to achieve the doping of the IrO2-RuO2 active layer with an ionic liquid having surfactant properties and a bismuth nitrate catalyst. The activity of the modified iridium ruthenium titanium mesh electrode is significantly improved, and the service life is significantly increased;
[0010] (2) The modified iridium ruthenium titanium mesh used in the present invention effectively enhances the adsorption capacity of the anode material for pollutants, while increasing the active sites of the electrode plate, thereby improving the efficiency of difficult-to-degrade organic pollutants in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Among them, (a) is a scanning electron microscope image of a Ti substrate, (b) is a scanning electron microscope image of an iridium ruthenium titanium mesh electrode (Ti / IrO2-RuO2), (c) is a scanning electron microscope image of an iridium ruthenium titanium mesh electrode modified by doping bismuth nitrate (Ti / IrO2-RuO2(Bi)), and (d) is a scanning electron microscope image of an iridium ruthenium titanium mesh electrode modified by doping 1-ethyl-3-methylimidazolium tetrafluoroborate and bismuth nitrate (Ti / IrO2-RuO2(Bi+[Emim]BF4));
[0012] Figure 2 In the figure, (a) is the element distribution diagram of the surface of the iridium ruthenium titanium mesh electrode Ti / IrO2-RuO2(Bi) modified by bismuth nitrate doped by energy dispersive spectrometer (EDS); (b) is the element distribution diagram of the surface of the iridium ruthenium titanium mesh electrode Ti / IrO2-RuO2(Bi+[Emim]BF4) doped with 1-ethyl-3-methylimidazolium tetrafluoroborate and bismuth nitrate;
[0013] Figure 3 (a) is the chlorine evolution curve of the iridium ruthenium titanium mesh electrode, and (b) is the oxygen evolution curve of the iridium ruthenium titanium mesh electrode;
[0014] Figure 4 This is a graph showing the accelerated life test of the iridium ruthenium titanium mesh electrode in the present invention. DETAILED DESCRIPTION
[0015] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] Example 1: Preparation of Ti / IrO2-RuO2(Bi+[Emim]BF4) Electrode
[0017] Step 1: The electrode is based on titanium mesh. Polish with 180, 400, and 800 grit sandpaper to remove the surface oxide layer, and then ultrasonically clean it in pure water for 10 minutes. Put the mesh into a 10% sodium hydroxide solution and boil it at 85°C for 2 hours to remove the oil stains on the surface of the mesh. Wash the mesh repeatedly with pure water and soak it in a 10% oxalic acid solution at 85°C for 2 hours to make the surface of the titanium mesh uneven and even pitted. The oxide layer on the surface of the titanium mesh is completely removed, so that the titanium mesh has a uniform and rough surface. Finally, rinse the titanium mesh with pure water and store the pretreated titanium mesh in a 1% oxalic acid solution.
[0018] Step 2, prepare the electrode oxide coating by thermal decomposition. Dissolve a certain amount of ruthenium trichloride and chloroiridic acid in n-butanol to ensure that the mass (g) of the total compound and the volume (mL) of n-butanol are 1:50, and the mass ratio of the ruthenium trichloride and chloroiridic acid is 2:1. Add an appropriate amount of bismuth nitrate, and always keep the concentration of bismuth nitrate at 1mmol / L. Add ionic liquid [Emim] BF4 respectively, ultrasonically vibrate for 20min to fully dissolve it, and stir evenly for 1h to prepare the required coating liquid.
[0019] Step 3: After the pre-treated spare titanium mesh is cleaned and dried with pure water, the prepared coating liquid is evenly brushed on the pre-treated titanium mesh with a brush, and quickly moved into a 105°C drying oven for 10 minutes, and then moved into a 450°C muffle furnace for high-temperature calcination for 15 minutes. The above operation is repeated 10-20 times until the coating liquid is used up. Finally, calcine at 450°C in a muffle furnace for 1 hour and cool to room temperature to obtain a modified iridium ruthenium titanium mesh electrode.
[0020] Step 4: The electrochemical treatment condition is constant current. The anode plate is a modified iridium ruthenium titanium mesh electrode, and the cathode is a titanium mesh electrode. The electrode size is 10cm×10cm. The diamond mesh size on the cathode plate and the anode plate is 5mm×10mm. The distance between the two plates is 3cm. 550mL of HEDP solution with an initial concentration of 50mg / L is placed in the electrolytic cell, the electrolyte is 0.25mol / LNaCl, and the electrode working area is 5cm×10cm. The current density is 30mA / cm 2 Electrocatalytic oxidation degradation.
[0021] Among them, in step 2, 0 μL, 2.5 μL, 5 μL, 7.5 μL, and 10 μL of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode prepared with the ionic liquid [Emim]BF4 were added respectively. Under the same electrocatalytic treatment conditions, after 120 minutes of electrocatalytic degradation, the removal rates of HEDP were 74.29%, 82.72%, 84.22%, 79.92%, and 79.07%, respectively. Among them, the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode prepared with 5 μL of the ionic liquid [Emim]BF4 had the highest removal rate for the difficult-to-degrade organic matter HEDP.
[0022] Embodiment 2:
[0023] The performance characteristics of the modified iridium ruthenium titanium mesh electrode prepared by the preparation method described in Example 1 when the addition amount of the ionic liquid [Emim] BF4 is 5 μL are as follows:
[0024] From the scanning electron microscopy images of the samples ( Figure 1 ) It can be seen that the titanium matrix is not exposed on the surface of the modified iridium ruthenium titanium mesh electrode. The particle size of the [Emim]BF4 and Bi co-doped electrode crystals is smaller and the arrangement is denser, which can more effectively prevent the penetration of corrosive substances and protect the matrix from being exposed to the corrosive medium, thereby enhancing the corrosion resistance of the titanium matrix. The roughness of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode surface is improved, and the coating on the electrode surface is more tightly bonded to the substrate and is not easy to fall off, which greatly extends the service life of the electrode. At the same time, the stacking of the disc structure also increases the surface area of the anode surface, thereby increasing the number of active sites on the anode surface and improving the catalytic activity of the electrode.
[0025] From the element distribution of the sample EDS electrode surface ( Figure 2) It can be seen that the corresponding Ir and Ru energy spectrum peaks appear in the figure, proving that the main components of the active layer of the Ti / IrO2-RuO2 electrode have been successfully added to the electrode coating. From the content of each element in the total spectrum of the Ti / IrO2-RuO2(Bi) electrode surface measured by the spectrometer in Table 1, it can be seen that the atomic percentage of Ir and Ru on the surface of the Ti / IrO2-RuO2(Bi) electrode doped with Bi alone is 19.53%. From the content of each element in the total spectrum of the Ti / IrO2-RuO2(Bi+[Emim]BF4) electrode surface measured by the spectrometer in Table 2, it can be seen that the atomic percentage of Ir and Ru on the surface of the Ti / IrO2-RuO2(Bi+[Emim]BF4) electrode co-doped with Bi and [Emim]BF4 is 25.69%. This shows that the addition of ionic liquid is conducive to the formation of the iridium and ruthenium active layer. Table 3 shows the Bi element content in the Ti / IrO2-RuO2(Bi) and Ti / IrO2-RuO2(Bi+[Emim]BF4) coatings determined by ICP-OES method, indicating that the Bi element content in the Ti / IrO2-RuO2(Bi) and Ti / IrO2-RuO2(Bi+[Emim]BF4) electrodes are 2312.13 mg / kg and 4168.01 mg / kg, respectively, indicating that the Bi element is successfully doped in the electrode surface coating.
[0026] Table 1 The content of each element in the total spectrum of Ti / IrO2-RuO2(Bi) electrode surface determined by energy spectrometer
[0027]
[0028] Table 2 The content of each element in the total spectrum of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode surface by energy spectrometer
[0029]
[0030] Table 3 Results of inductively coupled plasma emission spectrometer testing the Bi element in iridium ruthenium electrode coating
[0031]
[0032] The better the chlorine evolution performance of the electrode, the more free chlorine is produced and the higher the oxidation efficiency. Therefore, the lower the chlorine evolution potential, the easier it is for the anode to produce active chlorine, so its ability to remove pollutants by electrocatalytic oxidation is higher. The intersection of the chlorine evolution curve and the horizontal axis is the chlorine evolution potential. The lowest chlorine evolution potential of the Ti / IrO2-RuO2(Bi+[Emim]BF4) electrode is 1.107V( Figure 3 a), indicating that the co-doped modified electrode has the best chlorine evolution performance. Co-doping of Bi and [Emim]BF4 can improve the electrocatalytic performance of Ti / IrO2-RuO2 electrode.
[0033] During the electrocatalytic oxidation process, the oxygen evolution reaction on the anode will lead to a decrease in current efficiency, and the formation of gas will cause defects such as pores and cracks in the coating, accelerating the failure of the electrode coating. The higher the oxygen evolution potential (OEP), the more difficult the reaction is to occur, which is more conducive to the electrocatalytic oxidation of the electrode. The highest oxygen evolution potential of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode is 1.233V ( Figure 3 b). The doping of Bi and [Emim]BF4 can inhibit the occurrence of oxygen evolution reaction and extend the service life of the electrode.
[0034] Example 3: Effect of Modified Iridium Ruthenium Titanium Electrode on Removal of HEDP from Wastewater
[0035] In the electrocatalytic system, the anode plate is an iridium-ruthenium-titanium mesh electrode, and the cathode is a titanium mesh electrode. The size is 10 cm × 10 cm, the diamond mesh size is 5 mm × 10 mm, and the distance between the two electrodes is 3 cm. 550 mL of HEDP solution with an initial concentration of 50 mg / L is placed in the electrolytic cell, the electrolyte is 0.25 mol / L NaCl, the electrode working area is 5 cm × 10 cm, and the current density is 30 mA / cm 2 . A modified iridium-ruthenium titanium mesh electrode was used for electrocatalytic oxidation degradation. After 120 minutes of degradation, the removal rates of HEDP in the four iridium-ruthenium electrode electrocatalytic systems of Ti / IrO2-RuO2, Ti / IrO2-RuO2([Emim]BF4), Ti / IrO2-RuO2(Bi), and Ti / IrO2-RuO2(Bi+[Emim]BF4) were 49.85%, 60.74%, 74.29%, and 84.22%, respectively. The Ti / IrO2-RuO2(Bi+[Emim]BF4) electrode prepared in Example 2 had the highest removal rate for HEDP. This shows that co-doping with bismuth and ionic liquid can significantly improve the removal rate of HEDP.
[0036] Example 4: Ti / IrO2-RuO2(Bi+[Emim]BF4) electrode to eliminate the HEDP effect in water
[0037] In the electrocatalytic system, the constant current treatment was performed. The anode plate was the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode prepared in Example 2, and the cathode was a titanium mesh electrode. The size was 10 cm×10 cm, the diamond mesh size was 5 mm×10 mm, and the distance between the two electrodes was 3 cm. The electrolyte was 0.25 mol / L NaCl, and the current density was 30 mA / cm 2 . Take 1L of actual reverse osmosis concentrated water and add it into the electrolytic cell, then add 50mg / L of HEDP. In the actual reverse osmosis concentrated water, SO4 2-The concentration exceeded 22000mg / L, and the system conductivity was as high as 84.4ms / cm. After 120min of electrocatalytic oxidation reaction, the removal rate of HEDP reached 86.09%, while the removal rate of HEDP in the pure water system under the same conditions was 82.18%, and the removal effect of the actual wastewater system at any time during the reaction was better than that of the pure water system. Therefore, electrocatalytic oxidation can effectively remove HEDP in high-salt reverse osmosis concentrated water. The high salt content in reverse osmosis concentrated water provides a natural electrolyte for the electrocatalytic oxidation treatment process, and the high conductivity promotes the degradation of pollutants.
[0038] Example 5: Accelerated life test of modified iridium ruthenium titanium mesh electrode
[0039] The electrode was subjected to an accelerated service life test in a 1 mol / L H2SO4 solution. The effective area of the electrode in the electrolyte was 5 cm 2 , the current density is set to 1A / cm 2 The battery voltage was recorded periodically during the electrolysis process. When the battery voltage exceeded 10.0 V, the experiment was considered to be over. Figure 4 It shows that the battery potential of both Ti / IrO2-RuO2 and Ti / IrO2-RuO2(Bi+[Emim]BF4) electrodes remains at about 6V, but after 111h and 130h respectively, the battery potential of the two electrodes increases. According to the calculation formula of the actual service life of the electrode: Wherein T0 and T1 are respectively the accelerated and actual service life, I0 and I1 are respectively the accelerated and actual current density. Calculation shows that the actual service life of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode can reach 13000h, i.e. 542d, which is 1.2 times that of the unmodified electrode. The addition of Bi and [Emim]BF4 increases the service life of the Ti / IrO2-RuO2 electrode. Compared with Example 2, the morphology of the Ti / IrO2-RuO2 (Bi+[Emim]BF4) electrode has undergone significant changes. The optimized electrode has a smaller grain size, a relatively dense and stable surface structure, which enhances the corrosion resistance of the electrode and prolongs the service life of the electrode. The SEM results are consistent.
[0040] Therefore, the modified electrode Ti / IrO2-RuO2 (Bi+[Emim]BF4) not only has significantly improved electrochemical performance and electrocatalytic oxidation ability, but also has excellent stability and increased service life, and has high application value in the actual wastewater treatment field.
[0041] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a modified iridium ruthenium titanium mesh electrode, characterized in that: The following steps are involved: Step 1: Use titanium mesh as a substrate, remove the surface oxide layer, and make the surface of the titanium mesh present an uneven and uniformly rough surface; Step 2: dissolving ruthenium trichloride and chloroiridic acid in n-butanol, adding bismuth nitrate and 1-ethyl-3-methylimidazolium tetrafluoroborate to fully dissolve to obtain a coating solution; Step 3: Evenly coat part of the coating liquid on the surface of the titanium mesh, dry it and then calcine it at high temperature, repeat the steps of coating-drying-high temperature calcination until the coating is completed, and calcine it at high temperature for the last time to obtain a modified iridium ruthenium titanium mesh electrode.
2. The preparation method according to claim 1, characterized in that: In step 2, the volume ratio of the total mass of the ruthenium trichloride and chloroiridic acid to n-butanol is 1:50 g / mL, and the mass ratio of the ruthenium trichloride and chloroiridic acid is 2:
1.
3. The preparation method according to claim 1, characterized in that: In step 2, the concentration of bismuth nitrate in the coating solution is 1 mmol / L, and the concentration of 1-ethyl-3-methylimidazolium tetrafluoroborate in the coating solution is 2.35 mmol / L.
4. The preparation method according to claim 1, characterized in that: In step 3, the temperature of each drying treatment is 105°C and the time is 10 minutes, and the temperature of high-temperature calcination after drying treatment is 450°C and the time is 15 minutes; After coating, the last high temperature calcination temperature is 450°C and the time is 1h.
5. The preparation method according to claim 1, characterized in that: In step 1, the titanium mesh was polished with 180, 400, and 800 grit sandpapers to remove the surface oxide layer.
6. The preparation method according to claim 1, characterized in that: In step one, the titanium mesh with the surface oxide layer removed is placed in a 10% by mass sodium hydroxide solution and boiled at 85°C for 2 hours to remove oil stains on the surface of the mesh; the mesh is repeatedly washed with pure water and immersed in a 10% by mass oxalic acid solution at 85°C for 2 hours to make the surface of the titanium mesh uneven and even pitted, and the oxide layer on the surface of the titanium mesh is completely removed, so that the titanium mesh has a uniform and rough surface.
7. The preparation method according to claim 1, characterized in that: In step three, the coating-drying-high temperature calcination is repeated 10-20 times.
8. An application of a modified iridium ruthenium titanium mesh electrode prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The modified iridium ruthenium titanium mesh electrode is used as an anode plate in electrocatalytic oxidation, and the cathode plate in the electrocatalytic oxidation is a titanium mesh electrode.
9. The use according to claim 8, characterized in that: The size of the anode plate and the cathode plate is 10 cm×10 cm, the size of the diamond mesh on the cathode plate and the anode plate is 5 mm×10 mm, and the distance between the two plates is 3 cm.
10. The use according to claim 9, characterized in that: The target pollutant of the electrocatalytic oxidation is an organic phosphine scale inhibitor.